2019
DOI: 10.3390/antibiotics8030140
|View full text |Cite
|
Sign up to set email alerts
|

Tobramycin Promotes Melanogenesis by Upregulating p38 MAPK Protein Phosphorylation in B16F10 Melanoma Cells

Abstract: Tobramycin is an aminoglycoside-based natural antibiotic derived from Streptomyces tenebrarius, which is primarily used for Gram-negative bacterial infection treatment. Although tobramycin has been utilized in clinical practice for a long time, it has exhibited several side effects, leading to the introduction of more effective antibiotics. Therefore, we conducted our experiments focusing on new possibilities for the clinical use of tobramycin. How tobramycin affects skin melanin formation is unknown. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Activation of the MAPK p38 melanogenic pathway was also reduced by the decrease in p38 phosphorylation. Previous studies have shown how inhibition of p38 phosphorylation induces a decrease in the expression of tyrosinase and melanin in murine melanocytes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the MAPK p38 melanogenic pathway was also reduced by the decrease in p38 phosphorylation. Previous studies have shown how inhibition of p38 phosphorylation induces a decrease in the expression of tyrosinase and melanin in murine melanocytes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The plates were then shaken well on a shaker, and the absorbance was measured at 540 nm. The percentage of cell viability was determined according to a previously described method [14,31].…”
Section: Measurement Of Cell Viabilitymentioning
confidence: 99%
“…Melanin content in B16F10 cells was assayed according to a previously described method with a slight modification [14,31]. Cells at 1 × 10 5 were seeded in 60-mm dishes and incubated for 24 h. After that, the cells were treated with new medium containing 200 nm α-melanocyte-stimulating hormones (α-MSH) and FDS at various concentrations and incubated for 72 h. Next, the medium was carefully removed, and the cells were washed with cold phosphate-buffered saline.…”
Section: Measurement Of Melanin Contentmentioning
confidence: 99%
See 2 more Smart Citations